Research note: Methods in studying university youth in Kazakhstan - Kaplan, C.; Nassimova, G.; Brady, H. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2019)
The article presents new methods for the research of student youth in Kazakhstan and the basis of their implementation. The approaches used in the analysis of the political culture of student youth of Kazakhstan were developed in the framework of a research project supported by the Ministry of Education and Science of the Republic of Kazakhstan. The basic principles used in the construction of the survey sample and the development of the questionnaire, along with the determination of the number of students required in the sample needed to obtain the requisite information is described. Students at 10 institutions of higher education in Kazakhstan were surveyed with the number of respondents totaling 1161. The basic questions and problems encountered by the authors in the process of research are presented. The need for purposeful sampling is provided. The size of the sample makes possible the use of regression analysis. A description of how weights were created for the presentation of descriptive statistics is given. All of this made it possible to obtain data for determining and explaining the level of political activeness among students in Kazakhstan, their level of trust in political institutions, and the study of political values among student youth. Key words: methods, sample, regression analysis, questionnaire, youth, students.